2022
DOI: 10.1038/s41467-022-31363-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat-fueled enzymatic cascade for selective oxyfunctionalization of hydrocarbons

Abstract: Heat is a fundamental feedstock, where more than 80% of global energy comes from fossil-based heating process. However, it is mostly wasted due to a lack of proper techniques of utilizing the low-quality waste heat (<100 °C). Here we report thermoelectrobiocatalytic chemical conversion systems for heat-fueled, enzyme-catalyzed oxyfunctionalization reactions. Thermoelectric bismuth telluride (Bi2Te3) directly converts low-temperature waste heat into chemical energy in the form of H2O2 near room temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Typically, combining the triple mutant VV/A184V with IC5P for 48 h gave o ‐cresol with a TTN of 41 165, which was almost 13‐fold higher than that achieved with the corresponding 30 min reaction [TON: 3 073 (30 min) −1 P450 −1 ] and was comparable to the best result of NAD(P)H‐dependent P450 monooxygenase reported to date (Figure S25) [22, 43] . Ethylbenzene hydroxylation gave the highest TTN (80 963) for ( S )‐1‐phenylethan‐1‐ol by combining the double mutant VI with IC5P (Figures S26–S27), far better than any natural or engineered P450 monooxygenases previously reported, [41, 44] which was only lower than the best performing peroxygenase Aae UPO assisted by in situ generation of H 2 O 2 [45–48] . ( R )‐indan‐1‐ol obtained by combination of the quadruple mutant TV/A82T/L181M with IC5P achieved a TTN of 36 067 (Figures S30–S31).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Typically, combining the triple mutant VV/A184V with IC5P for 48 h gave o ‐cresol with a TTN of 41 165, which was almost 13‐fold higher than that achieved with the corresponding 30 min reaction [TON: 3 073 (30 min) −1 P450 −1 ] and was comparable to the best result of NAD(P)H‐dependent P450 monooxygenase reported to date (Figure S25) [22, 43] . Ethylbenzene hydroxylation gave the highest TTN (80 963) for ( S )‐1‐phenylethan‐1‐ol by combining the double mutant VI with IC5P (Figures S26–S27), far better than any natural or engineered P450 monooxygenases previously reported, [41, 44] which was only lower than the best performing peroxygenase Aae UPO assisted by in situ generation of H 2 O 2 [45–48] . ( R )‐indan‐1‐ol obtained by combination of the quadruple mutant TV/A82T/L181M with IC5P achieved a TTN of 36 067 (Figures S30–S31).…”
Section: Resultsmentioning
confidence: 53%
“…[22,43] Ethylbenzene hydroxylation gave the highest TTN (80 963) for (S)-1-phenylethan-1-ol by combining the double mutant VI with IC5P (Figures S26-S27), far better than any natural or engineered P450 monooxygenases previously reported, [41,44] which was only lower than the best performing peroxygenase AaeUPO assisted by in situ generation of H 2 O 2 . [45][46][47][48] (R)-indan-1-ol obtained by combination of the quadruple mutant TV/A82T/L181M with IC5P achieved a TTN of 36 067 (Figures S30-S31). The milligramscale reaction of ethylbenzene (15 mM) was finally verified using VI (0.5 μM) in the presence of IC5P (500 μM) and H 2 O 2 (20 mM) in 20 mL of 0.1 M phosphate buffer (pH 8.0) at 4 °C for 48 h. The results indicated that > 84 % ethylbenzene was consumed and (S)-1-phenylethan-1-ol was isolated as a colorless liquid (25.3 mg, 69.1 %) with high regioselectivity (> 99 %) and enantioselectivity (> 99 % ee) but accompanied with small amount of overoxidized phenylethanone (< 6 %) (Figures S34-S36).…”
Section: Resultsmentioning
confidence: 99%
“…The reaction solution was composed of 2.5 g/L catalyst, 15 mM substrate, and 150 mM methanol (MeOH) in phosphate buffered saline (PBS, pH = 7, 60 mM, 10 mL) at 25 °C, 12 h, and simulated sunlight. The total turnover number (TON) and turnover frequency (TOF) of r Aae UPO were calculated according to eqs and , respectively, as follows normalT normalO normalN normalr A a e normalU normalP normalO = normalc normalo normaln normalc normale normaln normalt normalr normala normalt normali normalo normaln .25em normalo normalf .25em normalp normalr normalo normald normalu normalc normalt normalc normalo normaln normalc normale normaln normalt normalr normala normalt normali normalo normaln .25em normalo normalf .25em normalr A a e normalU normalP normalO normalT normalO normalF normalr A a e normalU normalP normalO .25em ( min 1 ) = normalt normalu normalr normaln normalo normalv normale normalr .25em normaln normalu normalm normalb normale normalr normalr normale normala normalc normalt normali normalo normaln .25em normalt normali normalm normale …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The reaction solution was composed of 2.5 g/L catalyst, 15 mM substrate, and 150 mM methanol (MeOH) in phosphate buffered saline (PBS, pH = 7, 60 mM, 10 mL) at 25 °C, 12 h, and simulated sunlight. The total turnover number (TON) and turnover frequency (TOF) of r Aae UPO were calculated according to eqs and , respectively, as follows …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The unbiased PEC reaction is further combined with enantioselective oxyfunctionalization of C–H bonds using unspecific peroxygenase from Agrocybe aegerita, which was expressed recombinantly in Pichia pastoris (r Aae UPO). Selective oxyfunctionalization of (inert) C–H bonds is the long-standing goal in chemistry because the reaction offers novel synthetic strategies applicable to ubiquitous C–H bonds , in organic compounds (e.g., alkane feedstocks, pharmaceuticals).…”
mentioning
confidence: 99%